Hubungan Tingkat Konsumsi Energi Dan Status Gizi Dengan Daya Tahan Otot Atlet Judo Di Satria Jaya Judo Club Kota Denpasar - Ida Ayu Putu Putri Saraswati; I Wayan Ambartana; I Ketut Kencana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Muscle endurance is the ability of muscles to make repetitive movements over a period of time. The purpose of research is to find out about relathionship of energy consumption level and nutritional status with the muscular endurance of judo athlete in Satria Jaya Judo Club Denpasar City. Type of observational research by cross sectional design. The study sample was 58 people by the simple random sampling method. Data collected in the form of sample characteristics, muscular endurance, obtained from the results of muscle endurance 24 people (41,4%) in the excellent category and 2 people (3,4%) in the less category. From the results of energy consumption level of 27 people (46,6%) in the normal category and 5 people (8,6%) in the very poor category. From the results of nutritional status of 40 people (69,0%) in the normal category and 6 people (10,3%) in the obesity category. Pearson correlation test results showed a significant value of 0,00 0,01 that there is a significant relationship, the level of strength and direction of muscle strength with consumption. Kendall’s correlation test results showed a significant value of 0,003 0,01 that there is a significant relationship, the level of strength is quite strong and reversed between muscular endurance and nutritional status. The conclusion of this study is that there is a relationship of energy consumption level and nutritional status with the muscular endurance of judo athlete.Keywords: Muscular Endurance, Energy Consumption Level, Nutritional Status